Maqasid shariah in modern biotechnology concerning food products - Mohd Kashim, Ahmad Izhar Ariff; Muhammad Husni, Ahmad (UKM, 2017)
The development of modern biotechnology in food occurs rapidly simultaneously with the development of other technologies. As a result, a wide range of modern foods using biotechnology engineering technique has been produced. It is also recognisable, modern food that produced through this technique has its advantages and disadvantages. However, there are some products that are produced by mixing the halal (clean) and haram (unclean) things. Therefore, it raises doubt on Muslims whether it is permissible in Islam or not. Thus, a descriptive, comparative, and content analysis of the fiqh (maqasid sharia) and science (biotechnology) sources have been carried out so that the product meets the syarak (law). Through the study, any food products produced through modern biotechnology, such as genetically modified foods must meet the criteria set by the texts (al-Quran and Sunnah) and also in accordance with the maqasid sharia. The products must be taken from halalan tayyiban (allowed and clean) sources. In addition, it must be beneficial to human health, life, finance, and so on without neglecting the halalan tayyiban principle. Besides, it must be harmless to human because anything that bring harm to humans is forbidden in Islam.